Ecological networks to unravel the routes to horizontal transposon transfers - Venner, Samuel (PLoS Biol, 2017)
Transposable elements (TEs) represent the single largest component of numerous eukaryotic genomes, and their activity and dispersal constitute an important force fostering evolutionary innovation. The horizontal transfer of TEs (HTT) between eukaryotic species is a common and widespread phenomenon that has had a profound impact on TE dynamics and, consequently, on the evolutionary trajectory of many species' lineages. However, the mechanisms promoting HTT remain largely unknown. In this article, we argue that network theory combined with functional ecology provides a robust conceptual framework and tools to delineate how complex interactions between diverse organisms may act in synergy to promote HTTs.